Artesunate-driven autophagy: a shield against liver hypoxia/reoxygenation insult in rats via modulation of GLP1R, the chief metabolic kinase AMPK, mTOR, ULK1, P70S6K, cyclin D1, Akt, and GSK3β - Mai El-Sayed Ghoneim; Hanan S. El-Abhar; Dalaal M. Abdallah (SpringerOpen, 2024)
Abstract Background Hepatic hypoxia/reoxygenation (H/R) insult is a critical issue in hepatic transplant and surgeries, profoundly influencing postoperative prognosis. One crucial pathomechanism in this condition is impaired autophagy flux, which disrupts liver homeostasis. Artesunate, an antimalarial drug, has shown potential in providing hepatoprotection against H/R injury; however, whether it can modulate disrupted autophagy to enhance hepatoprotection remains unclear. Purpose of the study Accordingly, we delved into the potential mechanism(s) through which artesunate modulates the autophagy process in a hepatic H/R injury model. Methods and results Rats were categorized into three groups, viz. sham operated, H/R, and artesunate-treated (50 mg/kg, i.p). Disease regression was evaluated microscopically, and molecular alternations were assessed biochemically using ELISA and western blotting techniques. Mechanistic analysis revealed that artesunate administration at reperfusion time significantly upregulated the gene expression of GLP1R protein expression of p-AMPK, accompanied by a downregulation in those of p-mTOR, and its target molecule p-ULK1, presenting the first trail to initiate autophagy. Additionally, artesunate reduced H/R-induced hepatic upregulated protein expression of p-mTOR/P70S6K cue, and cyclin D1 content, which positively correlated with the mTOR/P70S6K axis. Moreover, artesunate sharply upregulated active p-Akt, which in turn phosphorylated/inactivated GSK3β, a cascade that indirectly promotes autophagy. Consequently, artesunate increased the hepatic beclin-1 and LC3-II to further uphold its autophagic capacity. The hepato-therapeutic effectiveness of artesunate was further evidenced by reduced serum ALT and AST levels, along with diminished hepatic histopathological alterations. Conclusion Artesunate protected liver by triggering autophagy partly by modulating the GLP1R/AMPK/mTOR/ULK1, GLP1R/AMPK/mTOR/P70S6K, cyclin D1, and Akt/GSK3β trajectories providing a significant therapeutic potential in managing hepatic H/R insult.